Antimicrobial resistance of Staphylococcus aureus isolated from the intensive care unit of a general hospital in southern Brazil - Jairo L. Hoerlle; Adriano Brandelli (Journal of Infection in Developing Countries)
Background: Staphylococcus aureus is recognized as a major cause of nosocomial infections worldwide. The aim of this study was to evaluate the antimicrobial resistance of S. aureus isolates and the possible changes of the resistance patterns after the implementation of norms of hospital infection control. Methodology: During the period of 2001 to 2004, antimicrobial resistance of S. aureus (n = 104) isolated from patients in the intensive care unit of the Hospital Divina Providencia (Porto Alegre, Brazil) was determined. The progress of S. aureus control in this hospital through 2002, after the implementation of norms for infection control, was also evaluated. Results: The glycopeptides presented larger in vitro activity against the isolates of S. aureus (100% of susceptibility for vancomycin and teicoplanin). The percentage of samples showing resistance to at least one drug was 96%, 97% and 100% for the years 2001, 2003 and 2004, respectively. Except for ampicillin and penicillin, antimicrobial resistance decreased from 2001 to 2004. A total of 26 phenotypic profiles were identified; among them a single profile (phenotype B) was identified in all three years of investigation, corresponding to 50% of the isolates. The number of isolated S. aureus decreased the following years, totaling 50 in 2001, 34 in 2003, and 20 in 2004. Conclusions: A reduction in the number of isolates and antimicrobial resistance of S. aureus from the intensive care unit was observed after the implementation of norms for infection control.